INcreasing Adolescent social and Community supporT (INACT): Pilot study protocol. - Daniel Hayes; Alexandra Burton; Feifei Bu; Neil Humphrey; Pamela Qualter; Emeline Han; Lou Sticpewich; Joely Wright; Jessica K Bone; Sophia Maguire; Lucas Caetano Gonzalez Umpierrez; Emily Stapley; et al. (PLoS ONE)
Background Social prescribing is a mechanism for connecting patients with non-medical forms of support within the community and has been shown to improve loneliness. Yet uptake from young people (YP) has been lower than for adults. That is thought to be the case because young people are less likely to engage with primary care for wellbeing support, where social prescribing is based. The INACT study will pilot a social prescribing pathway via schools to support young people who are lonely, testing its feasibility and acceptability of delivering, and evaluating its impact on loneliness through a randomised controlled trial. Methods This pilot study utilises a two-group (intervention vs. active control) parallel randomised design, with YP as the unit of randomisation. Approximately 78 pupils reporting loneliness will be recruited across 12 mainstream (6 primary and 6 secondary) schools in England. The co-produced social prescribing intervention includes 6-12 sessions over an 8-week period with a Link Worker who will work with individuals, on a one-to-one basis, to understand 'what matters to them' and connect them with local sources of support. Pupils in the control group will receive signposting to sources of support from school staff. Data will be collected at baseline, 3- and 6-month follow-up. Acceptability and feasibility will be assessed via participant recruitment and retention, and via qualitative interviews. Interviews will also explore barriers and facilitators to engagement and implementation and mechanisms of change. Primary and secondary outcomes will be completed to assess response and completeness, including measures of loneliness, mental health and wellbeing. Discussion The INACT study will provide preliminary evidence of the feasibility and acceptability of both the research design and social prescribing intervention. Results will inform a planned future randomised trial. Trial registration ClinicalTrials.gov NCT06656663.